Characteristics of Concrete With Rice Husk Ash Local Kutai Kartanegara - syahrul, syahrul (Universitas Negeri Semarang, 2022)
Abstract. Concrete material made from natural waste was developed to balance the use of concrete materials resulting from natural exploration with an impact on environmental damage, rice husk is a waste material from rice mills and contains reactive silica and has the benefit of reducing energy consumption in cement production. Laboratory test method in the form of testing the compressive characteristics used standard cube concrete 150 mm x 150 mm x 150 mm with a total sample of 24 samples. The effect of concrete strength on the amount of cement replacement is 0%; 5%; 10% ; and 15% which could be compared with concrete without using husk ash. The compressive strength obtained in terms of the age of the concrete is 28 days. The mechanical properties of husk ash at the age of 28 days gave optimal compressive strength results with the addition of 5% husk ash.